6
$\begingroup$

$$ \arctan\left(\frac{1}{1+n+n^2}\right)$$

My professor wrote this as

$$\arctan(n+1) - \arctan(n)$$

I don't understand how this expression is right?

$\endgroup$
  • $\begingroup$ Try taking tangent of both sides and using the tangent angle addition/subtraction formula. $\endgroup$ – Eric Auld May 30 '15 at 18:04
13
$\begingroup$

Use the formula

$$\tan(\alpha-\beta)=\frac{\tan\alpha-\tan\beta}{1+\tan\alpha\tan\beta}$$

with $\alpha=\arctan(n+1)$ and $\beta=\arctan n$.

$\endgroup$
10
$\begingroup$

See this diagram (drawn for $n=3$, but the principle is general):

Diagram goes here

The red line has slope $\dfrac{1}{1+n+n^2}$ and makes an angle of $\tan^{-1}(n+1)-\tan^{-1}(n)$ with the horizontal axis.

$\endgroup$
9
$\begingroup$

$$ \arctan x + \arctan y = \arctan \frac{x+y}{1-xy} $$ Applying this with $x=n+1$ and $y=-n$ we get $$ \frac{x+y}{1-xy} = \frac{(n+1)-n}{1+(n+1)n} = \frac 1 {n^2+n+1} $$

$\endgroup$
1
$\begingroup$

We have $$\tan^{-1}\left( \frac{1}{1+n+n^2}\right)$$ $$=\tan^{-1}\left( \frac{(n+1)-n}{1+n(n+1)}\right)$$ Now, let $\color{blue}{n+1=\tan\alpha}$ ($\implies \color{blue}{\alpha=\tan^{-1}(n+1)}$) & $\color{blue}{n=\tan\beta}$ ($\implies \color{blue}{\beta=\tan^{-1}(n)}$) $\forall \quad \alpha>\beta$

Thus by sustituitng the correspoding values in above expression, we get $$\tan^{-1}\left( \frac{\tan \alpha-\tan\beta}{1+\tan\alpha\tan \beta}\right)$$ $$=\tan^{-1}\left( \tan(\alpha-\beta)\right)$$$$=\alpha-\beta $$ $$=\color{green}{\tan^{-1}(n+1)-\tan^{-1}(n)}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.